The Effect of Interval Training and Fartlek Exercises on Increasing VO2 Max in Cadets Aged 15–17 at SMK Mitra Sehat Mandiri Sidoarjo - Faza Abid Elhaliqie; Muhammad Wahyono; Ramadhani Hananto (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to determine the effect of interval training and fartlek exercises on improving VO₂max in adolescents aged 15–17 years at Taruna Pelayaran SMK Mitra Sehat Mandiri Sidoarjo. This research employed a quantitative method using a one-group pretest–posttest design. The sample consisted of 27 students who received treatment in the form of an interval training and fartlek exercise program over a specific period. VO₂max was measured using the bleep test before and after the intervention.The results of the data analysis showed a significant increase in the average VO₂max score. Hypothesis testing using a paired sample t-test indicated a significance value of 0.000 (p < 0.05), meaning that there was a significant difference before and after the treatment. Based on these findings, it can be concluded that interval training and fartlek exercises have a significant effect on improving VO₂max in adolescents aged 15–17 years